SOSIALISASI LITERASI KEUANGAN DAN PENTINGNYA MENABUNG SEJAK USIA DINI SERTA PEMBUATAN CELENGAN DARI KARDUS BEKAS PADA SISWA SD NEGERI 001 PELALAWAN - Melisa Ambarwati; Fika Azzahra; Syakirah Athiyyah Fitri; Tuah Hidayat; Aisyah Alfi Ananda; Giovanni Nurfadhillah; Melani Noviantori Ramadhan; Zawa Hilya; Fitri Nurjannah; Salsalina Purba; Nelfa Valianti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Financial literacy remains an underdeveloped fundamental skill among elementary school students in Indonesia—specifically in Pelalawan Village—where students tend to spend their entire daily allowance without the habit of setting aside a portion for savings. This community service initiative aimed to enhance financial literacy understanding and instill a saving habit from an early age among students at SD Negeri 001 Pelalawan. The program was conducted over two days using an educational-participatory approach combined with hands-on learning; activities included interactive presentations on currency recognition, the